24‐3: Hot‐Melt‐Type Face‐Sealing Encapsulation for Flexible OLEDs. Issue 1 (30th May 2018) - Inoue, Hiroyasu; Murata, Naoki; Harai, Kenichi; Kashiwagi, Motofumi
Abstract : We have developed a face sealing sheet of flexible OLED in which hygroscopic particles are dispersed, based on a hot melt type adhesive. By using this sheet in combination with a gas barrier film, degradation of emitting area of OLED was suppressed. Also, it offers transparency, flexibility and adhesion.